Penerapan Model Project Based Learning Untuk Meningkatkan Motivasi Belajar Peserta Didik Kelas III Sekolah Dasar SDN 26 Cakranegara - Nurdina, Nurdina; Solihin, Solihin; Aminundin, Aminundin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This research aims to obtain information on the extent to which student motivation and learning outcomes increase by implementing the project-based learning model. The problem formulation in this research is